2015
DOI: 10.5530/jyp.2015.2.4
|View full text |Cite
|
Sign up to set email alerts
|

ABC and VED Analysis of the Pharmacy Store of a Tertiary Care, Academic Institute of the Northern India to Identify the Categories of Drugs Needing Strict Management Control

Abstract: Aim: To conduct ABC, VED and ABC-VED matrix analysis of the pharmacy store of the tertiary care, teaching, research and referral institute of the Northern India to identify the categories of drugs needing strict management control. Method: The ABC and VED (vital, essential, desirable) 19%, 19.83% and 9.98% of ADE of the pharmacy. VED analysis showed 12.30%, 61.5% and 26.2% items as V, E, and D category items, respectively, accounting for 19.56%, 71.12% and 9.33% of ADE of the pharmacy. However ABC analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
(6 reference statements)
1
16
0
4
Order By: Relevance
“…10 Additionally, Singh et al and Kant et al reported the ABC and VED matrix analysis systems should be adopted for optimal and rational use of resources and elimination of out-of-stock situations in hospital pharmacy. 28,29 Kokilam et al suggested the problems associated with stock-outs and wastage can be minimized upon implementation of corrective measures in the areas of procurement, drug quantification, distribution, and inventory control. 30 …”
Section: 23mentioning
confidence: 99%
“…10 Additionally, Singh et al and Kant et al reported the ABC and VED matrix analysis systems should be adopted for optimal and rational use of resources and elimination of out-of-stock situations in hospital pharmacy. 28,29 Kokilam et al suggested the problems associated with stock-outs and wastage can be minimized upon implementation of corrective measures in the areas of procurement, drug quantification, distribution, and inventory control. 30 …”
Section: 23mentioning
confidence: 99%
“…Certain parameters such as discounts by initial payment and ordering large quantity, etc. are also not considered in the inventory model.ABC and VED analysis identifies the drugs requiring stringent control for optimal use of funds and elimination of out-of-stock situations in the pharmacy 3 . The combined FSN and VED analysis to find the non-moving items which are less critical.…”
Section: Inventory Analysismentioning
confidence: 99%
“…ABC ve VED analizlerinin kombine edilerek ABC-VED Matrisi (Khurana et al, 2013:10;Gupta et al, 2007: 326-327) ) Yiğit et al 2010) (Khurana et al, 2013) (Devnani et al2010) (Roy et al, 2010) (Wandalkar et al .2013) (Basukala et al, 2015) (Mani, et al, 2014) ) (Pund et al 2016) (Singh et al, 2015) (Pirankar et al, 2014) …”
Section: Abc-ved Matris Analizimentioning
confidence: 99%